Typology of Uzbek and English Myths and Mythological Images - Shirinova Fotima (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
This article highlights general information about the myth genre, the etymology of this term and the history of it. Furthermore, this article is devoted to the typological study of myth and mythological images. The study illustrates comparative analysis of Uzbek and English myth and mythological images.